Cultural Needs of Inhabitants of Lithuania: Evaluation and Attendance of Cultural Institutions - Kublickienė, Lilija (Sociologija. Mintis ir veiksmas, 2004)
The article is devoted to the problems of cultural sociology. Methodological premises and actual directions of sociological research on culture are discussed. The importance and practical advantage of investigation of cultural needs of inhabitants is stressed. The aim of the paper – to describe actual cultural needs of Lithuanian inhabitants presenting repre sentative and statistically reliable data on their at tendance and evaluation of varies cultural institutions.According to the data obtained the most positive ratings and highest attendance is given to such cultural institutions or events as festivals/fairs and concerts. It was ascertained that the necessity of some cultural institutions is not directly related with their attendance. The interdependence between cultural needs and age, education level and living location of respondents is analysed.
Keywords: culture; cultural needs; cultural institutions